The importance of local long-duration STEM mentorship as a global mechanism for increasing diversity at all levels of education - Gallagher Dunn, Sarah Louise; Haviland, Heidi Fuqua; Gallagher, Dennis Lee (Frontiers in Astronomy and Space Sciences, 2023)
The space physics community is understandably and justifiably drawn to address the evident systemic biases found in the hiring and funding of researchers. It is our perspective that these rare representatives of diverse communities are more precious than may be appreciated in that they survived early life experiences to become researchers from a dramatically reduced pool of potential researchers (leaky pipeline). Their professional barriers are real and must be addressed. Yet, at the same time, they tend to obscure the profound underlying societal loss of the youngest, who could not overcome the barriers that prevented them from exploring who they could become. We identify and discuss possible issues within the traditional formal education and developmental environment of young inquiring minds, including gaps in resources, the pressure to bring in income during secondary school and graduate school matriculation, and the cultural biases against research careers. As a mitigation plan, we highlight and promote the importance of local mentorship and age-appropriate student chapters of professional organizations within all levels of education, including Kindergarten through bachelor's and advanced degree programs, as a means of overcoming barriers to becoming a respected contributing member of the space physics research community. We note these issues extend beyond space physics into all STEM fields. These student chapters can provide road maps into research careers, practice age-appropriate skills, and provide an avenue for current researchers to become mentors.